Relaxation processes in nonstoichiometric YBa₂Cu₃O₇-δ single crystals during annealing and at high pressure - Obolenskii, M.A.; Vovk, R.V.; Bondarenko, A.V. (Functional Materials, 2005)
The critical temperature relaxation processes and resistivity for YBa₂Cu₃O₇-δ single crystals with oxygen deficit δ ≤ 0,5 during annealing at room temperature and in case of
high hydrostatic pressure up to 7 kbar have been studied. It is shown that Тс(δ) dependence evolution during annealing is in satisfactory agreement with the existing theoretic models. When the samples with oxygen deficit δ ≤ 0,5 are kept under pressure at room temperature, the carriers number for low-temperature phase reduces, while the opposite process of holes number increase takes place in the high-temperature phase. The authors have determined the activation energy and characteristic times for relaxation processes for isobaric and isothermal exposure of the studied samples. Исследованы процессы релаксации критической температуры и электросопротивления монокристаллических образцов YBa₂Cu₃O₇-δ с дефицитом кислорода δ ≤ 0,5 в условиях отжига при комнатной температуре, а также в случае приложения высокого гидростатического давления до 7 кбар. Показано, что эволюция зависимости Тс(δ ) в процессе отжига удовлетворительно согласуется с существующими теоретическими моделями. В случае выдержки образцов с дефицитом кислорода δ ≤ 0,5 под давлением при комнатной температуре число носителей для низкотемпературной фазы уменьшается, в то же время, для высокотемпературной фазы происходит обратный процесс увеличения количества дырок. Определены энергия активации и характерные времена релаксационных процессов в случае изобарической и изотермической выдержки исследуемых образцов. Дослiджено процеси релаксацiї критичної температури та електроопору монокристалiчних зразкiв YBa₂Cu₃O₇-δ з дефiцитом кисню δ ≤ 0,5 в умовах вiдпалювання при кiмнатної температури, а також у разi докладання високого гiдростатичного тиску до 7 кбар. Показано, що еволюцiя залежностi Тс(δ) у процесi вiдпалювання задовiльно узгоджуеться з iснуючими теоретичними моделями. У разi витримування зразкiв з дефiцитом кисню δ ≤ 0,5 пiд тиском при кiмнатнiй температурi кiлькiсть носiїв для низькотемпературної фази зменшується, водночас для високотемпературної фази вiдбувається зворотний процес збiльшення кiлькостi дiрок. Визначено енергiю активацiї та характернi термiни процесiв релаксацiї за умов iзобаричного та iзотермiчного витримування зразкiв, що дослiджувалися.